Analisis Manajemen Pemasaran Islam terhadap Loyalitas Nasabah pada PT. BPRS Carana Kiat Andalas - Fauziah (El-kahfi | Jurnal Ekonomi Islam, 2023)
This study aims to find out how the application of Islamic marketing management at BPRS Carana Kiat Andalas to customer loyality and whether the marketing mix of BPRS Carana Kiat Andalas which consists of product, price, place and promotion can significantly increase customer loyalty. The object of this research is BPRS Carana Kiat Andalas. The method used in this study is a quantitative method with a questionnaire technique with a sample of 100 customers. The analytical method used is descriptive analysis, multiple linear test, R2 test, F test, and T test with product (X1), price (X2), place (X3), promotion (X4), and customer loyalty (Y). The results showed that product, price, place, and promotion simultaneously affected customer loyalty at BPRS Carana Kiat Andalas. From the results of the t test it was concluded that the price variable had a positive and significant effect on customer loyalty, while products, places and promotions had no significant effect on customer loyalty at BPRS Carana Kiat Andalas. This is proven based on partial calculations for tcount on product variables (1.192), price (1.745), place (-2.241), and promotion (-1.609). Meanwhile, the coefficient of determination R2 is 0.053 which implies that the influence of the independent variables on the dependent variable at BPRS Carana Kiat Andalas is 5.3% while the rest is influenced by other variables. BPRS Carana Kiat Andalas has implemented marketing management in accordance with Islamic economic principles.